2020
DOI: 10.1371/journal.pone.0231175
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influencing factors of the unsafe driving behaviors of online car-hailing drivers in china

Abstract: Online car-hailing drivers are a special group between professional drivers and private car drivers. The paper built the unsafe driving behavior model of online car-hailing drivers based on the theory of planned behavior (TPB), explored the socio-psychological factors underlying drivers' motivation for unsafe driving behavior and examined how these factors predict their behaviors. 239 online car-hailing drivers were surveyed with a self-reported questionnaire. Factors analysis proved the TPB questionnaire to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In comparison to men, we found that this factor received almost double the loading. The perceived behavior control factor finding also agrees with Razmara et al [15] and Xiao [14]. Attitude (severity) also influenced riding as reported by Bazargan-Hejazi et al [16].…”
Section: Discussion Of the Tpbsupporting
confidence: 87%
See 2 more Smart Citations
“…In comparison to men, we found that this factor received almost double the loading. The perceived behavior control factor finding also agrees with Razmara et al [15] and Xiao [14]. Attitude (severity) also influenced riding as reported by Bazargan-Hejazi et al [16].…”
Section: Discussion Of the Tpbsupporting
confidence: 87%
“…This finding is supported by Bazargan-Hejazi et al [16] and Nguyen et al [31], who found that attitude had the greatest effect on riding behavior. The next most influential factor was perceived behavior control, in agreement with Xiao [14], Razmara et al [15] and Bazargan-Hejazi et al [16], who both reported the direct and indirect effects of this factor on the theory of planned behavior (TPB). Although we only found a direct influence, attitude (severity) was also found to influence riding as was also reported by Bazargan-Hejazi et al [16].…”
Section: Discussion Of the Tpbsupporting
confidence: 79%
See 1 more Smart Citation
“…Online ride-hailing refers to the business activities of providing non-cruise booking taxi service based on a service platform that integrates information of supply and demand relying on Internet technology [ 1 ]. Compared with the traditional taxi, it has the advantages of high efficiency, good experience, convenience, and low price [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Online ride-hailing refers to the business activities of providing non-cruise booking taxi service based on a service platform that integrates information of supply and demand relying on Internet technology [1] .…”
Section: Introductionmentioning
confidence: 99%